UJI AKTIVITAS ANTIBAKTERI EKSTRAK BUAH MENGKUDU (Morinda citrifolia L.) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli, Salmonella thypi, Staphylococcus aureus dan Staphylococcus epidermidis - Febri Sembiring; Gabriella Septiani Nasution; Nita Andriani Lubis; yuli yantika syahputri (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Noni fruit (Morinda citrifolia L.) is one part of the Noni plant that contains metabolite compounds that are antibacterial. The antibacterial compounds produced are known to inhibit the growth of disease-causing bacteria. The purpose of this study was to measure the antibacterial activity of various concentrations of noni fruit extract against the growth of Escherichia coli, Salmonella thypi, Staphylococcus aureus and Staphylococcus epidermidis in vitro using the disc diffusion method. The results of this study indicate that the lowest concentration of Noni Fruit extract (60% v/v) can inhibit the growth of all types of bacteria tested. From the four test bacteria, the largest inhibition zone was found on Escherichia coli with a size of 23.05 mm at a concentration of 80% v/v Noni Fruit extract.